Resiliensi Anggaran Pembinaan Relawan Pencarian dan Pertolongan: Optimalisasi Pooling Fund Bencana Berdasarkan Peraturan Presiden Nomor 75 Tahun 2021 - Hasrian Hasrian; Fathin Aulia Rahman; Abdul Haris Achadi (Trends in Applied Sciences, Social Science, and Education, 2026)
The high level of multi-hazard threats in Indonesia demands a comprehensive disaster management system, one of which is through the strategic function of the National Search and Rescue Agency (Basarnas) in coordinating SAR Potentials. There is an incongruity between the constitutional obligation to protect lives and budget realities, evidenced by a 52.34% budget cut for the capacity building of SAR Potentials in the 2026 Fiscal Year due to expenditure adjustment directives. Empirically, this efficiency impacts the degradation of operational resilience and potentially hinders response time. Therefore, this study aims to analyze the impact of the budget efficiency policy and formulate an alternative funding resilience design, specifically through the integration of the Disaster Pooling Fund (PFB) instrument. To achieve this objective, this research employs a normative-empirical qualitative method with a legal policy analysis approach. The results indicate that pre-disaster preparedness expenditure is a strategic investment that triggers a multiplier effect based on the Value of Statistical Life (VSL) method. However, access to alternative funding is hindered by conflicting authoritative interpretations regarding pre-disaster classification and the bureaucratic complexities of the Pre-Validation Evaluation (PVE) and the Environmental and Social Management System (ESMS). The study recommends regulatory harmonization among Basarnas, the National Disaster Management Agency (BNPB), and the Ministry of Finance to optimize the PFB instrument. Bureaucratic simplification and the establishment of the SAR Potential capacity building nomenclature as a mandatory pre-disaster expenditure are necessary to protect the safety of citizens' lives.